Pengalaman Auditor, Independensi, Skeptisisme Profesional, Time Pressure, dan Red Flags Pengaruhi Kemampuan Deteksi Kecurangan Laporan Keuangan : (Studi Kasus pada Auditor di Kantor Akuntan Publik Wilayah Tangerang Selatan) - Canggah Wiarta (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the influence of auditor experience, independence, professional skepticism, time pressure, and red flags on the auditor's ability to detect financial statement fraud in the Public Accounting Firm (KAP) in the South Tangerang region. Data was collected through the distribution of questionnaires using the purposive sampling method, with a sample of 45 auditors from four KAPs. Data analysis was carried out using multiple linear regression with the help of SPSS software version 21 and Microsoft Excel 2021. The results showed that professional skepticism had a significant negative effect on the auditor's ability to detect fraud. On the contrary, auditor experience and red flags have a significant positive influence on auditor ability. Meanwhile, independence and time pressure do not have a significant influence on the auditor's ability to detect financial statement fraud.